India Transport Report Volume III Sector Reports Part II - Planning Commission (Planning Commission, 2013)
The most important reason why development of ports is critical to India’s economy is that Indian ports handle over 95 per cent of the country’s total international trade volume and around 70 per cent of total trade value. India’s 7,517-km coastline has 212 ports, and the quality of our ports has a significant influence on the cost structure of India’s exports and defines its competitiveness in the global market.
Moving India To 2032
National Transport Development Policy Committee